Comparative study on flexible link aerator using arduino programming and dissolved oxygen meter - Anuar, Fatin Farhana; Md Zain, Badrul Aisham; Al-Shaibani, Najib (UTHM, 2018)
Aerator machine is widely used in agricultural sector for maintaining the production and increasing the productivity. The flexible link aerator can be used at tiger prawn pond which is suitable as it only touches the surface of water to generate dissolved oxygen. The flexible link aerator needs improvement on the operation controlling of generating dissolved oxygen to increase the productivity of aquatic lives. Flexible link aerator is one of the machines for producing standard quality water for aquatic lives. Aquatic organism depends on dissolved oxygen for survival. Arduino is the controller unit of the aerator system for controlling the level of dissolved oxygen. To reduce the steady state error the PID is attached together to the aerator system. The model tank is filled with 8 liters, 12 liters and 16 liters of water for analysing the dissolved oxygen. The flexible link aerator is operating on Arduino to get the result based on it before comparing the result of dissolved oxygen meter. The measurement of dissolved oxygen level is based on the dissolved oxygen level set on Arduino. The results from 8 liters, 12 liters and 16 liters of water by using dissolved oxygen meter , and . The results by using Arduino system are , and at 8 liters, 12 liters and 16 liters of water. The Arduino controller program and the dissolved oxygen meter show its difference in value as the dissolved oxygen meter is considering the temperature.